Rational-Legal Bureaucracy and Religious-Relational Logics in ‎Madrasah Administration: A Qualitative Case Study at MTs II ‎Lubuklinggau - Syaiful Bahri; Murni Yanto; Sahib, Abdul (JPI: Jurnal Pustaka Indonesia, 2026)
Educational administration is a critical pillar in ensuring effective governance within Islamic educational institutions. Administrative systems in madrasahs are frequently influenced by personal relationships and traditional organizational culture, challenging the principles of rationality and legality. This study aims to analyze the implementation of Max Weber’s rational-legal bureaucracy model in educational administrative governance at Madrasah Tsanawiyah (MTs) II Lubuklinggau, focusing on the application of rationality, legality, and professionalism principles in administrative practice. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with six key informants, participant observation across three months, and analysis of official madrasah documents including SOPs, organizational charts, and meeting minutes. Data analysis followed the interactive model of Miles, Huberman, and Saldaña (2014), comprising data reduction, data display, and conclusion drawing/verification. Data validity was ensured through source triangulation, method triangulation, and time triangulation, supplemented by member checking and audit trail procedures. The findings reveal that MTs II Lubuklinggau substantially reflects Weber’s rational-legal bureaucracy principles through its hierarchical structure, formal division of labor, documented regulations, and rule-based decision-making. However, implementation remains inconsistent, particularly in inter-unit coordination and periodic performance evaluation. Notably, the study identifies a distinctive adaptive model in which Weberian formality is organically integrated with Islamic values such as ikhlas (sincerity), musyawarah (deliberation), and moral accountability, resulting in what this study terms a "religious-rational bureaucracy" model. This finding contributes a new theoretical perspective on bureaucratic adaptation in Islamic education contexts and has practical implications for madrasah governance reform.